2015
DOI: 10.1038/nchem.2327
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of vibrational control of light-induced charge transfer in donor–bridge–acceptor assemblies

Abstract: Nuclear-electronic (vibronic) coupling is increasingly recognized as a mechanism of major importance in controlling the light-induced function of molecular systems. It was recently shown that infrared light excitation of intramolecular vibrations can radically change the efficiency of electron transfer, a fundamental chemical process. We now extend and generalize the understanding of this phenomenon by probing and perturbing vibronic coupling in several molecules in solution. In the experiments an ultrafast el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
126
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 50 publications
(62 reference statements)
3
126
1
Order By: Relevance
“…Recent efforts led by Rubtsov et al,12,13 Bakulin et al, 14 and our group 15,16 have shown that one way to experimentally exploit vibronic coupling to modulate molecular function is to introduce targeted vibrational excitation along specific reaction co-ordinates using ultrafast mid-infrared (IR) pulses. This approach enables promoting or suppressing electronic transitions, notably photo-induced electron transfer (ET), an elementary process that pervades the natural world.…”
Section: Main Textmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent efforts led by Rubtsov et al,12,13 Bakulin et al, 14 and our group 15,16 have shown that one way to experimentally exploit vibronic coupling to modulate molecular function is to introduce targeted vibrational excitation along specific reaction co-ordinates using ultrafast mid-infrared (IR) pulses. This approach enables promoting or suppressing electronic transitions, notably photo-induced electron transfer (ET), an elementary process that pervades the natural world.…”
Section: Main Textmentioning
confidence: 99%
“…Figure 2b displays the 2DIR spectrum in the ground electronic state of 1* at an IR pump -IR probe delay of 3 ps. Negative-positive peak pairs along the diagonal correspond to de-population of the ground state and associated population of the v=1 state, giving rise to ground state bleaching, stimulated emission (v=1 0), and excited state absorption (v=1 2) red-shifted from the ground state bleach by the vibrational anharmonicity (typically ~ 20 cm -1 for C C stretches in Pt-acetylides 16 ). Coupling between the ( 12 C) and ( 13 C) vibrations would appear as off-diagonal (cross-) peaks.…”
Section: Vibrationally Decoupling the Two Electron Transfer Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Even in this well-understood limit different considerations apply under different conditions, and different levels of descriptions were applied to account for the molecular nature of the solvent (89), the dimensionality of the process (90)(91)(92)(93)(94)(95)(96)(97)(98)(99), and the definition of the reaction coordinate. Extensions to equilibrium situations have ranged from considerations of deviation from transition state theory (TST) to the description of control by external fields (99)(100)(101).…”
mentioning
confidence: 99%